Maternal socio-economic status determines animal source food consumption of children aged 6–23 months in East African countries: a multilevel mixed-effects generalized linear model - Mussa, Ibsa; Gamachu, Mulugeta; Regassa, Lemma Demissie; Birhanu, Abdi; Mohammed, Fethia; Weyessa, Alemayehu Deressa; Eyeberu, Addis; Debela, Adera; Zakaria, Hamdi Fekredin (Frontiers in Nutrition, 2024)
Background: Nutrient deficiencies in Africa persist due to limited access to animal-source foods, causing a higher undernutrition prevalence, with 30.7% stunted children under five, which is higher than the global average of 22.0%. In African regions, there needs to be more information on access, consumption, and factors influencing children's animal-source food consumption.Therefore, we comprehensively analyse data from the Demographic and Health Surveys (DHS) to determine factors associated with children's (aged 6-23 months) consumption of animal-source foods (ASFs) in East African countries, which is crucial for policy and program development.We utilized cross-sectional pooled DHS data from nine East African countries reported from 2015 to 2021. The sample size consisted of 18,686 weighted children aged 6-23 months who were included. The DHS data were collected from women (15-49 years old) from households in each enumeration area of each country. We calculated the pooled proportion of consumption of foods of animal origin using multi-level logistic regression analysis to determine factors of ASFs, and the strength of the association was measured by an adjusted odds ratio (AOR) with a 95% CI and a p-value<0.05, which was declared as a significant.The study found that 51.07% (95% CI: 50.26%-51.88%) of infants and young children in East Africa consume ASFs, with variation across countries, of which 28.26% (95% CI: 26.31%-30.29%) was the lowest in Burundi and 55.81% (95% CI: 53.39%-58.21%) was the highest ASF consumption in Zimbabwe. The amount of ASF consumed grows with children's age and varies greatly between countries. In addition, children in the wealthiest quintile and with the highest educational attainment consume more ASFs. However, those who lived in rural areas consumed fewer ASFs.: The consumption of ASFs increased with the age of children, maternal education, and household wealth index. The government and non-government sectors should implement public health interventions targeting rural residents and poor households to increase access to and consumption of ASFs for children aged 6-23 months in East Africa.